The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1467-8462.12298
|View full text |Cite
|
Sign up to set email alerts
|

Violence in the Household and Happiness in Mexico

Abstract: This article has two purposes: first to investigate whether violence influences wellbeing; second to investigate whether the effect of violence is greater for women than for men. The results show that there is a significant impact on the wellbeing of individuals when suffering violence from someone with whom they live, with women being more severely affected than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Mexico is one of the countries in Latin America and the Caribbean with high levels of structural violence in its society (Charles-Leija et al, 2019 ). A high prevalence of violence directed at women from men is often observed due to the machismo ingrained in the different spheres of Mexican society (Moral & Ramos, 2016 ).…”
Section: Contextual Factors Of Chile and Mexico During The Covid-19 Pandemicmentioning
confidence: 99%
“…Mexico is one of the countries in Latin America and the Caribbean with high levels of structural violence in its society (Charles-Leija et al, 2019 ). A high prevalence of violence directed at women from men is often observed due to the machismo ingrained in the different spheres of Mexican society (Moral & Ramos, 2016 ).…”
Section: Contextual Factors Of Chile and Mexico During The Covid-19 Pandemicmentioning
confidence: 99%
“…However, when the dependent variable (life satisfaction) is categorized into High and Low, personal security does turn out to be a statistically significant factor for life satisfaction, alongside other SWB indicators (table 3). The reason, which is also observable in the bubble diagram in figure 2, is that poor households appear to perceive the problem of security more acutely than higher-income households (Charles-Leija et al, 2018). By analyzing it at the household level, the problem of security manifests itself more among the poor in disadvantaged neighborhoods in which QoL and happiness is compromised by a plethora of impediments to well-being.…”
Section: Discussionmentioning
confidence: 94%
“…According to an econometric analysis by Rojas (2018a), satisfaction with life declines in the presence of perceptions of corruption and exposure to crime, these results coincide with those of Martinez-Martinez et al (2018). Charles-Leija et al (2018) report that violence disproportionally affects women, although stronger social and family networks and better educations reduce the likelihood of physical assaults and violence. Not everything is a problem in Latin America, and public policy needs to recognize that family and community are a source of strength and inspiration (Rojas, 2018a;Rojas & Elizondo-Lara, 2012).…”
Section: Introductionmentioning
confidence: 89%
“…In a study conducted with 136 women who were victims of violence, it was determined that violence has a direct effect on psychological distress and an indirect effect on happiness (Bonilla‐Algovia et al., 2020). In another study conducted with men and women who were exposed to domestic violence, it was reported that violence negatively affects happiness levels in both genders, and women are more severely affected than men (Charles‐Leija et al., 2019).…”
Section: Discussionmentioning
confidence: 99%